2014
DOI: 10.3390/molecules191220731
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Dendriplexes by Ion Mobility-Mass Spectrometry

Abstract: Abstract:Highly branched polyamidoamine (PAMAM) dendrimers presenting biological activities have been envisaged as non-viral gene delivery vectors. They are known to associate with nucleic acid (DNA) in non-covalent complexes via electrostatic interactions. Although their transfection efficiency has been proved, PAMAMs present a significant cytotoxicity due to their cationic surface. To overcome such a drawback, different chemical modifications of the PAMAM surface have been reported such as the attachment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…It is now important for a consensus to emerge on this matter; a lack of clarity amongst those working with dendrimer drugs means that the hurdle for obtaining FDA regulatory approval for clinical trial testing is very likely to remain too high for others to achieve. In this specific context, the recent analytical work of French groups to reliably and reproducibly define the precise MWt of their dendrimers (with all of the challenges that this involves) using mass spec based analytical techniques is to be highly commended [14,15,36].…”
Section: Sulfate Modified Macromolecules For Hivmentioning
confidence: 99%
“…It is now important for a consensus to emerge on this matter; a lack of clarity amongst those working with dendrimer drugs means that the hurdle for obtaining FDA regulatory approval for clinical trial testing is very likely to remain too high for others to achieve. In this specific context, the recent analytical work of French groups to reliably and reproducibly define the precise MWt of their dendrimers (with all of the challenges that this involves) using mass spec based analytical techniques is to be highly commended [14,15,36].…”
Section: Sulfate Modified Macromolecules For Hivmentioning
confidence: 99%
“…Mass spectrometry analysis of intact polyanionic nucleic acids has nowadays acquired sufficient maturity to be considered as a method of choice for the structural investigation of nucleic acids, including nucleic acids complexed to dendrimers . In particular, ion mobility spectrometry (IMS) experiments represent an invaluable analytical method to generate structural data on gas-phase ions .…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Leriche et al studied for the first time dendriplexes by mass spectrometry methods, including collision-induced dissociation (CID) and ion mobility mass spectrometry experiments . Based on their CID data, the PAMAM/ds-DNA interaction was proposed to be only electrostatically driven, while for a phenyl-modified PAMAM, they suggested that intercalation also contributes to the dendrimer/ds-DNA binding . In that report, even if IMS experiments were conducted, no collision cross sections were provided and no MD simulations were presented to support the experimental-derived conclusions …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations